Acute Cholecystitis - Eachempati, Soumitra R.; Reed, II, R. Lawrence (Springer International Publishing : Imprint: Springer, 2015)
This text covers all aspects of the current diagnosis and treatment of acute cholecystitis. Different diagnostic tests are discussed as well as the preoperative evaluation needed to initiate treatment. Other sections include the management of acute cholecystitis in the critically ill and elderly patients, recent advances in operative strategies that have further altered the treatment of acute cholecystitis, and the utilization of routine intraoperative cholangiography and its relative merits.   Primarily intended for general surgeons and residents training in general surgery, Acute Cholecystitis will also serve as a comprehensive reference material for other health care providers, including primary care providers, mid-level nurse practitioners, emergency room physicians and medical students.  .